Argimou : A Legend of the Micmac - Huyghue, Douglas S., 1816-1891 (Early Canadian literature series., 2017)
Both an adventure-laced captivity tale and an impassioned denunciation of the marginalization of Indigenous culture in the face of European colonial expansion, Douglas Smith Huyghue?s Argimou (1847) is the first Canadian novel to describe the fall of eighteenth-century Fort Beauséjour and the expulsion of the Acadians. Its integration of the untamed New Brunswick landscape into the narrative, including a dramatic finale that takes place over the reversing falls in Saint John, intensifies a sense of the heroic proportions of the novel's protagonist, Argimou. Even if read as an escapist romance and captivity tale, Argimou captures for posterity a sense of the Tantramar mists, boundless forests, and majestic waters informing the topographical character of pre-Victorian New Brunswick. Its snapshot of the human suffering occasioned by the 1755 expulsion of the Acadians, and its appeal to Victorian readers to pay attention to the increasingly disenfranchised state of Indigenous peoples, make the novel a valuable contribution to early Canadian fiction. Situating the novel in its eighteenth-century historical and geographical context, the afterword to this new edition foregrounds the author's skilful adaptation of historical-fiction conventions popularized by Sir Walter Scott and additionally highlights his social concern for the fate of Indigenous cultures in nineteenth-century Maritime Canada.